Negotiating Cultural Identity, Hybridization, and Power Dynamics: A Study of Indian Song Cover Videos by Indonesian Singers - Romdhi Fatkhur Rozi; Kirti Dang Longani (Pusat Studi Gender Universitas Jember, 2026)
This study examines the phenomenon of Indian song cover videos produced by Indonesian women on the YouTube platform. It employs a qualitative approach using content analysis of popular cover videos and in-depth interviews with several cover singers as research subjects. The aim is to explore how this performance practice becomes an arena for the negotiation of cultural identity, hybridization, and power dynamics in the era of globalization. By utilizing the theoretical frameworks of hybridization by scholars like Homi Bhabha, Canclini and Pieterse also power-knowledge by Michel Foucault, this research finds the efforts of cover singers to adopt elements of Indian culture, such as singing style, choreography, costumes, and cinematography. The findings indicate that the mimicry practice performed by the cover singers is never entirely perfect. This process instead creates a space for hybridization where Indian and Indonesian cultural elements interact, resulting in a unique form of cultural expression. Furthermore, a Foucauldian analysis reveals that this phenomenon is not merely an act of appreciation but a manifestation of cultural power dynamics that operate subtly. This power works through aesthetic and performance norms disseminated by the popularity of Bollywood, which are then voluntarily self-disciplined and reproduced by the cover singers. Thus, this study argues that Indian song cover videos serve as evidence of how modern cultural identity is formed through a complex interaction of imitation, adaptation, and negotiation.